A three-phase community microgrid comprised of single-phase energy resources with an uneven scattering amongst phases - Shahnia, Farhad; Chandrasena, R. (Elsevier, 2017)
© 2016 Elsevier LtdThis paper considers a three-phase, low voltage community network with both grid-connected and autonomous modes of operation, which is composed of a group of residential houses and some single-phase, converter-interfaced distributed energy resources (DER) with equal and arbitrarily scattering of the DERs among the phases. The vigorous operation of such a microgrid system is examined with the proposed management techniques. In such a network, it is highly probable for one phase to have a high generation capacity while the other phases experience a higher demand; a technically challenging problem for a network operating in autonomous mode. In this paper, it is proposed for the single-phase DERs of such a system to operate under a droop-based voltage control technique while an appropriate technique is proposed to facilitate the transmission of the excess power from one phase to other phases. The proposals are validated by extensive digital simulations in PSCAD/EMTDC for several scenarios to demonstrate the feasibility of operating such a system and the efficacy of the proposed techniques.